Measurement invariance of the short form compassionate love scale for a romantic partner and sexuality - Neto, Joana Sequeira (2024)
Compassionate love (CL), a particular kind of love, is centred on enlarging beneficence to another. A short form to assess CL for a romantic partner (CLS-P-SF) was recently developed. The CLS-P-SF is a one-dimensional measure. In this study, we examined CLS-P-SF’s measurement invariance (MI) across gender and age, and the relationship of the CL with sexuality measures. There were 1184 Portuguese participants, 48% women and 52% men, aged between 18 to 79 (M = 37.36; SD = 16.89). Confirmatory factor analyses evidenced that the one latent dimension of the CLS-P-SF confirmed an acceptable fit to the data. MI, and internal consistency were adequate. This invariance permitted to perform meaningful latent average comparisons. The effect of gender and age were not significant. CLS-P-SF was positively associated with sexual desire, love is most important, sex demonstrates love, love comes before sex and satisfaction with sex life, and negatively associated with sex is declining and sociosexuality. Findings are discussed in their relationship with existent literature. The CLS-P-SF’s brevity makes it a promising tool for researchers and practitioners.